EIF2 alpha phosphorylation alleviates UVA-induced HO-1 expression in mouse epidermal cells. (2nd December 2018) - Xue, Fangfang; Chen, Shida; Chunxiang, Bian; Farrukh Nisar, Muhammad; Liu, Yong; Sutrisno, Linawati; Xiang, Yuancai; Zhang, Yiguo; Diao, Qingchun; Lin, Mao; Zhong, Julia Li
Abstract: Ultraviolet A (UVA) irradiation is a potential environmental stressor, which contributes to inflammation, photoaging, and carcinogenesis. UVA causes endoplasmic reticulum stress, hence phosphorylates the α subunit of eIF2. Meanwhile, UVA also induces expression of haem oxygenase-1 (HO-1) and nuclear factor erythroid-derived two related factor 2 (Nrf2) in human skin cells. In mouse JB6 cell, we found high dose UVA could change cell morphology, cause cell viability loss. UVA irradiation activated phosphorylation of eIF2α and Nrf2-HO-1 pathway in a dose-dependent manner. Besides, modulation of eIF2α phosphorylation status could alter expression pattern of Nrf2-HO-1 signalling. Salubrinal, a selective inhibitor of eIF2α dephosphorylation, increased the S phase in cell cycle of JB6 cells after UVA irradiation, suggesting phosphorylation status of eIF2α may affect cellular homeostasis under UVA irradiation. The study directed to further acknowledge about the relationship of UVA-induced eIF2α phosphorylation and Nrf2-HO-1 pathway, which may play a role in phototherapy and photo protection.